Myricetin inhibits pseudorabies virus infection through direct inactivation and activating host antiviral defense - Hu, Huaiyue; Hu, Zhiqiang; Zhang, Yingying; Wan, Hongping; Yin, Zhongqiong; Li, Lixia; Liang, Xiaoxia; Zhao, Xinghong; Yin, Lizi; Ye, Gang; Zou, Yuan-Feng; Tang, Huaqiao; et al. (Frontiers in Microbiology, 2022)
Myricetin, a polyhydroxyflavone compound, is one of the main ingredients of various human foods and therefore also known as dietary flavonoids. Due to the continuous emergence of resistant strains of herpesviruses, novel control measures are required. In the present study, myricetin exhibited potent antiviral activity against pseudorabies virus (PRV), a model organism of herpesvirus. The suppression rate could reach up to 96.4% at a concentration of 500 μM in cells, and the 50% inhibitory concentration (IC50) was 42.69 μM. Moreover, the inhibitory activity was not attenuated by the increased amount of infective dose, and a significant reduction of intracellular PRV virions was observed by indirect immunofluorescence. A mode of action study indicated that myricetin could directly inactivate the virus in vitro, leading to inhibition of viral adsorption, penetration and replication in cells. In addition to direct killing effect, myricetin could also activate host antiviral defense through regulation of apoptosis-related gene expressions (Bcl-2, Bcl-xl, Bax), NF-κB and MAPK signaling pathways and cytokine gene expressions (IL-1α, IL-1β, IL-6, c-Jun, STAT1, c-Fos and c-Myc). In PRV-infected mouse model, myricetin could enhance the survival rate by 40% at 5 days post infection, and viral loads in kidney, liver, lung, spleen and brain were significantly decreased. The pathological changes caused by PRV infection were improved by myricetin treatment. The gene expressions of inflammatory factors (MCP-1, G-CSF, IL-1α, IL-1β and IL-6) and apoptotic factors (Bcl-xl, Bcl-2 and Bax) were regulated by myricetin in PRV-infected mice. The present findings suggest that myricetin can effectively inhibit PRV infection and become a candidate for development of new anti-herpesvirus drugs.